THE ACMEOLOGICAL PARADIGM IN HIGHER EDUCATION: ACCELERATING FUNCTIONAL COMPETENCE AND PROFESSIONAL SELF-ACTUALIZATION IN PRE-SERVICE PEDAGOGUES (Multidisciplinary Journal of Science and Technology, 2026)
The transition from theoretical academic preparation to dynamic pedagogical mastery requires a profound restructuring of the future educator's internal motivational and cognitive frameworks. This study evaluates the precise pedagogical, psychological, and analytical outcomes of integrating a targeted acmeological methodology—the science of achieving professional developmental peaks—into the higher education curriculum, comparing it against conventional didactic instruction. A prospective, longitudinal, quasi-experimental pedagogical analysis was conducted involving 215 undergraduate students (3rd and 4th academic years) enrolled in pre-service teaching programs. Subjects were stratified into a conventional instructional cohort (n=105) reliant on standard lecture-seminar formats, and a targeted acmeological cohort (n=110) subjected to an intensive 18-month curriculum featuring individualized acmeograms, reflexive-analytical situational modeling, and continuous heuristic feedback loops. Empirical data indicate that passive knowledge accumulation frequently fails to generate the functional adaptability required in unpredictable classroom environments. The targeted acmeological cohort demonstrated a 48.6% relative acceleration in overall functional competence acquisition, directly correlating with a measured expansion of professional reflexivity scores from a baseline of 42.1 ± 3.4 to 81.5 ± 4.2 points on a standardized psychopedagogical index (p = 0.004). Conversely, the conventional group exhibited persistent plateaus in methodological agility and a significantly higher latency in resolving simulated pedagogical conflicts. The dynamics of the observed results suggest that isolated subject-matter expertise is fundamentally insufficient for modern teaching. Comprehensive higher education frameworks must actively integrate structured acmeological scaffolding to continuously drive the student's intrinsic drive toward self-actualization, optimizing the cognitive architecture necessary for lifelong professional evolution and elite pedagogical performance.